Monomolecular adsorption on nanoparticles with repulsive interactions: a Monte Carlo study - Pinto, Oscar Alejandro (2016)
In the present work, we study the adsorption of different monomolecular species on nanoparticles with different sizes and geometries using a grand canonical Monte Carlo method. These species are characterized by repulsive lateral interactions between themselves, as takes place in the case of the adsorption of partially charged atoms or molecules. Nanosize effects are analyzed in terms of adsorption on edge and facet sites. The energy minimization in these systems comes out as a complex conjugation of the repulsive lateral interactions between the adsorbates and the attractive interactions of the adsorbates with the nanoparticle. The phenomenon is analyzed as a function of the occurrence of different ordered structures being formed on the surface of the nanoparticle. We find that layers with different structures may coexist on different facets of the nanoparticle. Finally, a discussion of deposition on flat surfaces and in finite systems is given.